Analysis of Students’ Gramatical Error in Using Present Continuouse Tense - Septi Nurlela; Yanuar Dwi Prastyo; Imam Subari (International Conference on Education and Language (ICEL), 2013)
English is the first foreign language in formal school in Indonesia, it has been taught from kindergarten up to university. However, students still find difficulties in learning process because the language is different, and many English learners fail to learn English as foreign language. English consists of four skills they are listening, speaking, reading, and writing. And it has three components they are pronunciation, vocabulary, and grammar. Based on the writers experience as English teacher, one of the difficulties faced by students is grammar, and it is important for us to learn grammar. Here the students often produce many ungrammatical sentences. This paper is aimed at finding out whether the students make grammatical error in using present continuous tense or not, and to know the types of students’ grammatical error in using present continuous tense. The population of the research was the students of SMP Muhammadiyah I Teluk Betung at grade eight that consists of 34 students. Here, the writers used total sampling technique. In collecting the data the writers used translation test by asking the students to translate 10 sentences from Indonesian into English. The research found that the students’ errors in using present continuous tense were 91 from 340 sentences. There were 22 omission errors, 20 addition errors, 24 misformation errors, and 25 misordering errors, and the correct sentences were 249. It can be seen that the students’ addition errors were the lowest errors and the students’ misordering errors were the highest errors.